A new primate assemblage from La Verrerie de Roches (Middle Eocene, Switzerland). Issue 113 (December 2017) - Minwer-Barakat, Raef; Marigó, Judit; Becker, Damien; Costeur, Loïc
Abstract: Primates reached a great abundance and diversity during the Eocene, favored by warm temperatures and by the development of dense forests throughout the Northern Hemisphere. Here we describe new primate material from La Verrerie de Roches, a Middle Eocene karstic infill situated in the Jura Region (Switzerland), consisting of more than 80 dental remains. The primate assemblage from La Verrerie de Roches includes five different taxa. The best represented primate is Necrolemur aff. anadoni, similar in size and overall morphology to Necrolemur anadoni but resembling in some features the younger species Necrolemur antiquus . Microchoerines are also represented by two species of Pseudoloris, P. pyrenaicus and Pseudoloris parvulus, constituting the unique joint record of these two species known up to now. Remains of Adapiformes are limited to one isolated tooth of a large anchomomyin and another tooth belonging to the small adapine Microadapis cf. sciureus . The studied primate association allows assigning La Verrerie de Roches to the Robiacian Land Mammal Age. More specifically, this site can be confidently situated between the MP15 and MP16 reference levels, although the primate assemblage probably indicates some degree of temporal mixing. This is the first record of P. pyrenaicus and a form closely related to N. anadoni out of the Iberian Peninsula. The identification of these microchoerines in Switzerland gives further support to the connection of NE Spain and Central Europe during the Middle Eocene.